The software package MIEZEPY for the reduction of MIEZE data. (14th October 2019) - Schober, Alexander; Wendl, Andreas; Haslbeck, Franz X; Jochum, Johanna K; Spitz, Leonie; Franz, Christian
Abstract: Modulation of intensity with zero effort (MIEZE) is a neutron resonant spin echo technique which allows to measure the intermediate scattering function S ( Q, τ ) under depolarizing conditions. Since MIEZE produces a complex four dimensional dataset, we have developed the software package MIEZEPY to reduce the dataset and extract S ( Q, τ ) in a user friendly manner. This is an essential step in establishing the MIEZE technique and improving user operation. MIEZEPY was written in Python as an open source package and was developed on GitHub. In this paper the framework and implementation of this package as well as the physical and mathematical principles underlying the data reduction procedure will be introduced to lay out the complexity of this task.